Usability Considerations in Social Mobile Maps to Encourage Social Change - Silva Neto, André Avelino Da; Melo, Paulo Alves De; Barbosa, Estêvão; Mota, Marcelle (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2023)
Maps play an essential social role in serving as a basis for understanding phenomena and proposing social changes. The use of mobile devices is a possible solution to enhance the spread of these maps, given their practicality and familiarity with most of the users. However, using mobile maps has several usability challenges, many of which have already been investigated in others studies. When dealing with social maps, different challenges could be found, making it difficult to understand the mapped reality and, consequently, to make decisions. This research discusses usability in mobile social maps and aspects that can improve usability to visualize social data. For this, a study was carried out on usability in mobile maps. Usability tests were applied to a mobile application resulting from a project with social mapping. We also discuss how hypotheses raised by other authors may or may not be applied to social maps. As a result, we propose considerations that discuss how design decisions can support the stimulation of critical thinking about the social reality, aiming to encourage social change.